Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3349/ymj.2020.61.6.482
|View full text |Cite
|
Sign up to set email alerts
|

Does a Gradient-Adjusted Cardiac Power Index Improve Prediction of Post-Transcatheter Aortic Valve Replacement Survival Over Cardiac Power Index?

Abstract: Purpose: Cardiac power (CP) index is a product of mean arterial pressure (MAP) and cardiac output (CO). In aortic stenosis, however, MAP is not reflective of true left ventricular (LV) afterload. We evaluated the utility of a gradient-adjusted CP (GCP) index in predicting survival after transcatheter aortic valve replacement (TAVR), compared to CP alone. Materials and Methods: We included 975 patients who underwent TAVR with 1 year of follow-up. CP was calculated as (CO× MAP)/[451×body surface area (BSA)] (W/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…When calculating the augmented blood pressure, we assumed that adding the mean aortic valve gradient to the systemic systolic blood pressure can reflect the actual systolic pressure generated by the left ventricle (12). While noninvasive MAP is practically calculated as the summation of diastolic blood pressure and 1/3 pulse pressure, MAP also equals the product of cardiac output and systemic vascular resistance (SVR) (assuming a negligible central venous pressure level).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When calculating the augmented blood pressure, we assumed that adding the mean aortic valve gradient to the systemic systolic blood pressure can reflect the actual systolic pressure generated by the left ventricle (12). While noninvasive MAP is practically calculated as the summation of diastolic blood pressure and 1/3 pulse pressure, MAP also equals the product of cardiac output and systemic vascular resistance (SVR) (assuming a negligible central venous pressure level).…”
Section: Discussionmentioning
confidence: 99%
“…The augmented blood pressure calculation formulas are stated as below (12): Augmented SBP1(AugSBP1): Mean aortic valve gradient (mean AVG) was added to systolic blood pressure (Equation 1) and augmented MAP1(AugMAP1) was calculated by replacing the SBP with augmented SBP1 in the MAP formula (Equation 2); Valvulo-arterial impedance (Zva) was calculated according to the standard formula by dividing the sum of the systolic blood pressure and mean transvalvular gradient by stroke volume index (SVI)(Equation 3)(13).…”
Section: Calculation Of Augmented Mean Arterial Pressure and Valvulo-arterial Impedancementioning
confidence: 99%
“…Elevated Zva has been reported to be associated with worse quality of life and exercise performance at one year (10), while there are inconsistent results in predicting long-term mortality (14)(15)(16). Our group previously reported that cardiac power index and gradient-adjusted cardiac power index are good predictors of 1-year mortality after TAVR (6,7). In the calculation of gradient-adjusted cardiac power index, transvalvular gradient (mean transvalvular gradient or instantaneous peak transvalvular gradient) was added to the systolic blood pressure as augmented systolic blood pressure to calculate augmented mean arterial pressure (MAP).…”
Section: Background/introductionmentioning
confidence: 88%
“…2) Augmented SBP2(AugSBP2): Aortic valve maximal instantaneous gradient was added to systolic blood pressure (Equation 2), and augmented MAP2(AugMAP2) was calculated by replacing the SBP with augmented SBP2(Equation 4); and 3) Augmented MAP3(AugMAP3): Aortic valve mean gradient was added to mean arterial pressure (Equation 5) (6). Valvulo-arterial impedance (Zva) was calculated according to the standard formula by dividing the sum of the systolic blood pressure and mean transvalvular gradient by stroke volume index (SVI) (15).…”
Section: Calculation Of Augmented Systolic Blood Pressure Mean Arterial Pressure and Valvulo-arterial Impedancementioning
confidence: 99%
See 1 more Smart Citation